Bibliometric Analysis of PBL for Visual Communication Design Education: Theme Development and Opportunities for New Critical Thinking - Bt samsuddin, Yati (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to map the thematic development of research on Problem-Based Learning (PBL) in the context of Visual Communication Design (VCD) education linked to critical thinking and visual/creative thinking over the period 2015–2025, while identifying potential areas for research novelty. A bibliometric approach was employed by retrieving data using Publish or Perish (PoP) with Google Scholar as the data source and the following query: (